Understanding how Grade 11 Biology teachers mediate learning of respiration: A Namibian case study - Amutenya, Laina N (Rhodes University, Faculty of Education, Department of Education, 2015)
The new curriculum in Namibia has introduced a new approach to teaching and learning requiring teachers to make use of learners' prior everyday knowledge (PEK) including indigenous knowledge (IK) and practical work/activities. It further emphasizes some variations in teaching methods such as; the use of analogies, the use of mind maps, and so forth with the aim to actively involve learners in the learning process and develop skills to solve global challenges. The emphasis is on understanding of knowledge, skills and the will to use them appropriately throughout their lives. The main aim of this study was to understand and document how Biology teachers mediate learning of the topic respiration. Informed by an interpretive paradigm, a qualitative case study was conducted at two secondary schools in the Kunene region. The participants were selected using a convenience sampling. Data were gathered using three main sources, namely, documents, semi-structured interview questions which culminated into a questionnaire and observations. Triangulation was thus used to give credibility, objectivity and validity to the interpretation of the data. Data analysis in this case study involved a multi-stage process of organizing, coding and categorizing, synthesizing and summarizing. The audio recorded lessons were transcribed into text and I analyzed data using a colour coding technique by segmenting and labelling text to identify descriptions and broad themes in the data. Vygotsky's Mediation of Learning and Social Constructivism in conjunction with Shulman's Pedagogical Content Knowledge (PCK) informed the data analysis process. Teacher-learner interactions were the main theme for mediation of learning (social constructivist perspective), hence during analysis I paid more attention to moments where interactions evolved and I used PCK to gain insights in teaching and instructional strategies used by teachers. The findings of this study revealed that: 1) teachers endeavor to use a variety of teaching methods such as the use of a mind maps and question and answer method. Learners were keen to ask questions in order to understand this topic. 2) The study also revealed that a lack of practical activities is one of the challenges teachers are faced with. Based on my research findings, I therefore suggest that there is a need for continuous professional development of biology teachers and capacity building in order to improve both their content and pedagogical content knowledge.
Keywords: Biology -- Study and teaching (Secondary) -- Namibia; Respiration -- Study and teaching (Secondary) -- Namibia